Strategies for introducing titania onto mesostructured silica nanoparticles targeting enhanced photocatalytic activity of visible-light-responsive Ti-MSN catalysts - Abdul Rahman, Anis Farhana (Elsevier, 2017)
Titanium-mesostructured silica nanoparticles (Ti-MSN) catalysts which are excellent photocatalytic materials for the environment were prepared by supporting mesostructured silica nanoparticles (MSNs) with titanium species synthesized by three different approaches: microwave and in situ and ex situ electrochemical methods, denoted as Ti-MSN-M, Ti-MSN-I, and Ti-MSN-E, respectively. The physicochemical properties of the catalysts were investigated via XRD, 29Si NMR, N2 adsorption-desorption, FTIR, ESR, and UV-DRS analyses. Characterization results revealed that the introduction of mesoporous titania nanoparticles (MTNs) prepared by the microwave method onto MSNs (Ti-MSN-M) did not significantly affect the silica framework. However, the silica network in the Ti-MSN-I and Ti-MSN-E was rather disrupted, particularly for the former catalyst, due to the desilication accompanied by isomorphous substitution of Ti in the MSN framework to form Si[sbnd]O[sbnd]Ti bonds. Ti was also found to be exchanged with the terminal hydroxyl groups of all catalysts to form the Si[sbnd]O[sbnd]Ti bonds. The addition of Ti species onto MSNs also increased the number of oxygen vacancies (Vo) and metal defect sites. Photocatalytic testing on the decolorization of Congo red (CR) resulted in the following order: Ti-MSN-I (94%) > Ti-MSN-M (90%) > Ti-MSN-E (34%). The Vo and metal defect sites were responsible in lowering the band gap of catalysts and decreasing the electron–hole recombination, while the great numbers of Si[sbnd]O[sbnd]Ti bonds as well as large surface area and pore volume increased the active sites and offered a good surface contact with light to enhance the activity of catalysts. A kinetic study demonstrated that the photodegradation followed the pseudo-first-order Langmuir-Hinshelwood model. Ti-MSN-I and Ti-MSN-M maintained their activities for up to five runs without serious catalyst deactivation, indicating their potential for the degradation of dye in wastewater. Mineralization measurements of CR by TOC and BOD5 analyses after 3 h of contact time were 85.7% and 87.6% using Ti-MSN-M, while 83.7% and 80.3% using Ti-MSN-I, respectively. Optimization by response surface methodology showed that the catalyst dosage, pH, and TiO2 loading were the significant factors in the decolorization of CR. This study demonstrated that these two green technologies; electrochemical and MW have a great potential to be used in synthesis of various advanced materials for greener and more sustainable processes.